Lerna, a preclassical site in the Argolid : results of excavations conducted by the American School of Classical Studies at Athens.Volume VI, The settlement and architecture of Lerna IV - Banks, Elizabeth Courtney; American School of Classical Studies at Athens (Princeton, N.J.: American School of Classical Studies at Athens, 2013)
In 1995, Jeremy B. Rutter presented the pottery of the Fourth Settlement at Lerna in Lerna III: The Pottery of Lerna IV . The present volume is the companion to the Rutter volume, outlining the architectural sequence of the EH III period at the site with descriptions of the major building types and other features, such as hearths, ovens and bothroi. Careful examination of the individual buildings and their contents constitutes the core of the text. The changing settlement patterns of the site through time are considered and sources of influences are suggested.
Reproduction available: Electronic reproduction. Palo Alto, Calif. : ebrary, 2013. Mode of access: World Wide Web. System requirements: Adobe Acrobat Reader or other PDF reader (latest version recommended); Internet Explorer or other browser (latest version recommended).
Includes bibliographical references and index.
Keywords: Excavations (Archaeology) -- Greece -- Lerni; Land settlement patterns -- History. -- Greece -- Lerni; Architecture, Ancient -- Greece -- Lerni; Classical Greek & Roman archaeology ; European history: BCE to c 500 CE; Ancient Greece ; BCE to c 500 CE; Lerni (Greece) -- Antiquities